2005
DOI: 10.1111/j.1440-1827.2005.01900.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing 14‐3‐3 sigma expression with declining estrogen receptor α and estrogen‐responsive finger protein expression defines malignant progression of endometrial carcinoma

Abstract: 14-3-3 sigma (sigma) is a negative regulator of the cell cycle and contributes to G2 arrest. Lack of its expression due to hypermethylation of CpG islands has been reported in some carcinomas. A recent study showed that 14-3-3 sigma was down-regulated through proteolysis by estrogen-responsive finger protein (Efp). Here, we investigated the expression of 14-3-3 sigma, hormone receptors, Efp and p53 in 86 cases of endometrial adenocarcinoma and 46 cases of normal or non-neoplastic endometria by means of immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Immunohistochemical analysis of endometrial adenocarcinomas and normal endometrial tissue demonstrated increased Efp and estrogen receptor (ER) expression in endometrial adenocarcinomas (80). Increased Efp in cancer cells was inversely proportional with 14-3-3α levels in these samples.…”
Section: E2 and E3 Enzymesmentioning
confidence: 99%
“…Immunohistochemical analysis of endometrial adenocarcinomas and normal endometrial tissue demonstrated increased Efp and estrogen receptor (ER) expression in endometrial adenocarcinomas (80). Increased Efp in cancer cells was inversely proportional with 14-3-3α levels in these samples.…”
Section: E2 and E3 Enzymesmentioning
confidence: 99%
“…Previous studies in other tumors suggest that 14-3-3σ may be a prognostic marker, and high grade, advanced stage endometrial carcinomas over expressed 14-3-3σ when compared to low-grade lesions [13]. In these tumors, increased 14-3-3σ expression was correlated with hypomethylation of the CpG island.…”
Section: Discussionmentioning
confidence: 59%
“…Loss of 14-3-3σ expression in association with hypermethylation has also been reported in several other cancers, including ovarian [8], hepatocellular [9], prostate [10], some lung [11], gastric [12] and endometrial carcinomas [13]. It is important to point out that this is not the only mechanism for 14-3-3σ down-regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionality of MRC2 has also been implicated in prostate cancer progression (40). Higher SFN/14-3-3r expression has been reported in lung cancer (41), squamous cell carcinoma (42), pancreatic cancer (43) endometrial carcinoma (44), cervical cancer (45), and colorectal carcinoma (46) and appears to be associated with an overall worse prognosis. Specifically, higher SFN/14-3-3r expression significantly correlates with large tumor size and depth of invasion of vulva squamous cell carcinoma (42).…”
mentioning
confidence: 99%